Predicting Listed Firms’ Financial Statement Fraud Risk in the Vietnamese Securities Market - Chi, Bui Phuong; Thuy, Nguyen Thi Hong; Huong, Lang Trinh Mai (VNU JOURNAL OF ECONOMICS AND BUSINESS; Vol 37 No 1, 2021)
This paper focuses on fraud risk and identifying factors that affect the risk of financial reporting fraud of listed companies in Vietnam, and on forecasting the possibility of fraudulent financial statements of listed companies in Vietnam. Based on M-score and F-score models and an experimental survey of the research sample of 3,684 financial statements made by 307 companies in the period 2007-2008, the paper indicates that the higher the financial statements are, the more fraud occurs in the statements. Also, the older and larger the companies are, and the longer they have been listed on the stock exchange market, the more fraudulent their financial statements are likely to be.